Evaluation of the marginal adaptation of ceramic copings in function of the - Hilgert, Edson; Neisser, Maximiliano P.; Bottino, Marco A. (Brazilian Dental Science, 2010)
This study evaluates the marginal adaptation of ceramic copings (In-Ceram, Vita) front of two finish lines andinternal surface treatment (Rocatec, ESPE). For this, two master steel dies were milled with all-ceramic crownspreparation, one with a round shoulder (RS) margin design, and the other with a deep chamfer (DC). Twentycopings were made, and the marginal discrepancy was evaluated in measuring microscope, obtaining an initialmeasure. Each group was divided in two others, which received two kinds of silica sandblasting: (1) in all innercrown surface - DCt and RSt - and (2) in the inner crown surface, but preserving the cervical edge - DCa andRSa. The discrepancies were measured again and the data submitted to the statistical analysis. Marginal discrepancyvalues of 42,37±18,78μm were observed for group DC and 33,35±20,08μm for group RS in the initialmeasures, without significant statistical differences among them. The initial and final gap values were comparedto each one of the experimental groups, being observed statistical differences in DCa and DCt. Statistical differenceswas not observed among the post-sandblasting values. It was concluded that both cervical endings presentsimilar marginal adaptations between them when not submitted to any treatment type. When accomplishedthe surface treatment, negative influence was observed in the marginal adaptation of some groups, if comparedthe initial and final values, in spite of differences among the last ones were not been observed.